The impact of alliances and internal R&D on the firm's innovation and financial performance - Fábio de Oliveira Paula; Jorge Ferreira da Silva (BBR: Brazilian Business Review)
This paper intends to understand the relationships among internal and external R&D, innovation performance and financial performance in Brazilian manufacturing firms by testing a model using data from 2,810 firms. The study achieves this objective. We detected a positive relationship between external R&D from strategic alliances and innovation performance. Internal R&D, on the other hand, did not influence innovation performance directly; however, it positively moderated the relationship between strategic alliances and innovation performance, corroborating with the absorptive capacity theory. Contrary to our expectations, innovation performance had a negative influence on future financial performance. This was caused by the two-year lag between the measurement of the proxies of these two constructs, which was not long enough to allow identifying an increasing in revenues from new products and services. However, it captured the negative effect of redirecting marketing and sales resources for innovation activities, such as internal R&D, and of management costs of strategic alliances.